2016
DOI: 10.1007/s10509-016-2780-6
|View full text |Cite
|
Sign up to set email alerts
|

Spatially open Friedmann–Robertson–Walker Universe fueled with interacting sources

Abstract: In the present paper, we are analyzing the k = −1−FRW Universe with two interacting ideal fluids. The energy densities and the pressures are used to derive the corresponding Equations of State. For a particular form of the interaction term between the two fluids, it turns out that the Universe is filled with a mixture of dust and radiation.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…On the other hand, there is the opposite scenario which is consistent with the negatively curved FRW models: Gamma-ray halos around active galactic nuclei [10], the intergalactic magnetic field with the observation of TeV blazar 1ES 0229+200 [11], gamma-ray data [12], and strong magnetic filed from Fermi observations of TeV blazars [13]. Also the quintessence models with various potentials [14], and a nonlinear massive gravity with Lorentz-invariant mass terms have been studied in open FRW-Universe [15,16].…”
Section: Introductionmentioning
confidence: 77%
“…On the other hand, there is the opposite scenario which is consistent with the negatively curved FRW models: Gamma-ray halos around active galactic nuclei [10], the intergalactic magnetic field with the observation of TeV blazar 1ES 0229+200 [11], gamma-ray data [12], and strong magnetic filed from Fermi observations of TeV blazars [13]. Also the quintessence models with various potentials [14], and a nonlinear massive gravity with Lorentz-invariant mass terms have been studied in open FRW-Universe [15,16].…”
Section: Introductionmentioning
confidence: 77%
“…Recently, it has been shown that the observed large-scale cosmic microwave anomalies, discovered by WMAP and confirmed by the Planck satellite, are most naturally explained in the context of a marginally-open universe [39]. Also, there are several approaches, based on the string theory or quantum cosmology, in favor of the open universe [40]- [41]. Therefore sine now, we concentrate on the spatially open universe, i.e.…”
Section: (M )mentioning
confidence: 99%